Visceral Adiposity Index Is a Measure of the Likelihood of Developing Depression Among Adults in the United States - Lei, Jun; Luo, Yaoyue; Xie, Yude; Wang, Xiaoju (Frontiers in Psychology, 2022)
Background: Depression is a serious mental disorder often accompanied by emotional and physiological disorders. Visceral fat index (VAI) is the current standard method in the evaluation of visceral fat deposition. In this study, we explored the association between VAI and depression in American population using NHANES data. Methods: A total of 2577 patients were enrolled for this study. Data was collected through structured questionnaires. Subgroup analysis for the relationship between VAI and depression was evaluated using multivariate regression analysis after adjustment for potential confounding factors. Results: For every 1 unit increase in VAI, the clinical depression increased by 14% (OR=1.14, 95% CI: 1.04-1.25). High VAI scores (T3) increased the highest risk of developing depression (OR = 2.32, 95% CI: 1.2-4.47). Subgroup analysis demonstrated a strong and stable association between VAI and development of depression. Conclusions: Our study showed that depressive symptoms are associated with the high ratio of visceral adiposity index after controlling for confounding factors.